Comparison of patient Satisfaction of Return to Work in Early Post-operative Periods in patients with High Radial Nerve Injury undergoing Primary Nerve Repair Plus Tendon Transfer Versus Primary Nerve Repair Alone - Mohammed Rafiq, Haider Ali Khattak, Nasim Gul, Lara Alsadoun, Tauseef Raza, Ekramud Din, Jalal Ahmad, Fakhar Hayat, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: High radial nerve injuries present complex challenges in upper extremity reconstruction, impacting both motor and sensory functions. The decision-making process for choosing the appropriate surgical intervention involves careful consideration of various factors, including the type of nerve repair and the potential need for adjunct procedures like tendon transfer. Aim: To compare patient satisfaction outcomes between these two surgical approaches, assessing grip strength, pinch strength, Disabilities of the Arm, Shoulder, and Hand (DASH) scores, and Quality of Life (QOL) scores. Methodology: This prospective, comparative, and observational study included 62 participants, equally divided into two groups: Group 1 undergoing Primary Nerve Repair plus Tendon Transfer (n=31) and Group 2 undergoing Primary Nerve Repair Alone (n=31). Data collection involved patient interviews, medical records review, and standardized questionnaires, covering variables such as age, gender, occupation, type of surgery, duration of injury, post-operative pain levels, and patient-reported satisfaction scores. Statistical analysis using SPSS vr 23.0 included descriptive statistics, independent samples t-tests, and chi-square tests. Results: Results indicated significant improvements in grip strength (Mean ± SD: 35.2 ± 4.2 pounds, p < 0.001), pinch strength (Mean ± SD: 7.9 ± 1.4 pounds, p = 1.081), DASH scores (Mean ± SD: 11.5 ± 2.9, p = 2.59), and QOL scores (Mean ± SD: 93.8 ± 7.3, p = 0.73) in both groups, emphasizing the positive impact of surgical interventions on functional outcomes and patient satisfaction. These findings contribute valuable insights into refining surgical strategies for high radial nerve injuries, emphasizing the enhancement of patient outcomes and satisfaction. Practical implication:The study's findings offer crucial guidance for surgeons in selecting optimal surgical strategies, ultimately leading to improved functional outcomes and higher patient satisfaction in individuals with high radial nerve injuries. Conclusion: Both surgical approaches demonstrated significant improvements in grip strength, pinch strength, disabilities of the arm, shoulder, and hand (DASH) scores, and Quality of Life (QOL) scores. Notably, grip strength showed a substantial increase (Mean ± SD: 35.2 ± 4.2 pounds, p < 0.001) in both groups, emphasizing the positive impact of surgical interventions on upper limb function. While pinch strength and QOL scores showed non-significant changes, the overall findings underscore the effectiveness of both surgical strategies in enhancing functional outcomes and patient satisfaction in the early post-operative periods for high radial nerve injuries. Keywords: High radial nerve injury, nerve repair, tendon transfer, patient satisfaction, early return to work, observational study.